2012
DOI: 10.1002/ibd.21719
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of risk factors for diagnostic delay in inflammatory bowel disease

Abstract: Whereas the median delay for diagnosing CD, UC, and IC seems to be acceptable, there exists a long delay in a considerable proportion of CD patients. More public awareness work needs to be done in order to reduce patient and doctor delays in this target population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
208
4
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(256 citation statements)
references
References 30 publications
14
208
4
8
Order By: Relevance
“…A study by Vavricka et al 162 from the Swiss IBD Cohort Study group reported that among 1591 patients with IBD, median delay was 9 months in CD and 4 months in UC. Vavricka et al 162 noted that the delay could be because in patients with mild IBD, symptoms were similar to those of IBS. In one-quarter of patients with CD, the diagnosis took longer than 24 months, and in 10% it took 8 years or longer.…”
Section: Quality-of-life Summarymentioning
confidence: 99%
“…A study by Vavricka et al 162 from the Swiss IBD Cohort Study group reported that among 1591 patients with IBD, median delay was 9 months in CD and 4 months in UC. Vavricka et al 162 noted that the delay could be because in patients with mild IBD, symptoms were similar to those of IBS. In one-quarter of patients with CD, the diagnosis took longer than 24 months, and in 10% it took 8 years or longer.…”
Section: Quality-of-life Summarymentioning
confidence: 99%
“…The lack of data on stricture formation in EoE may be related to the fact that EoE is diagnosed with a longer diagnostic delay (time period from appearance of first symptoms to diagnosis, median 5 years in EoE) when compared with Crohn's disease (median 0.75 years). [7,15] During this long diagnostic M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…This study raises several discussion points including: (1) median time to diagnosis was less than that reported by the Swiss IBD cohort [1], probably related to easier access to the healthcare system in France than in other countries; and (2) the time to diagnosis associated with poor outcomes was C13 months, less than the proposed 18-24-month therapeutic window of opportunity for early disease [10,11]. This study confirms that any delay in CD diagnosis may result in higher surgical risk and probable lower efficacy of therapeutic strategies.…”
mentioning
confidence: 65%
“…The significance of diagnostic delay is that the postponement of the institution of effective treatment can profoundly affect patient well-being and overall disease evolution. The diagnosis of Crohn's disease (CD) is often delayed 5-9 months due to the variability and subtlety of its initial manifestations, as opposed to ulcerative colitis (UC), which due to its consistent initial symptoms and manifestations is usually diagnosed more rapidly [1,2]. Moreover, CD patients with pure ileal disease and age \40 at diagnosis are significantly at risk of considerable diagnostic delay ([24 months) [1], data confirmed by the results of the IMPACT survey among European patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation